Deotyma o natchnieniu pisarza - w "Pamiętniku 1834-1897" i "Zwierciadlanej zagadce" = Deotyma on the writer`s inspiration - based on "Memoirs 1834-1897" and "Zwierciadlana zagadka" ("The mirror riddle") - Budzanowska-Weglenda, Dominika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Jadwiga Łuszczewska (1834-1908) is considered a representative of the second generation of Romantics. In her memoir and fantasy novel "Zwierciadlana zagadka" ("The Mirror Riddle"), she explains how she understands literary inspiration. According to her, the work of a writer is hard, systematic and meticulous work carried out according to a plan given by inspiration.
Keywords: Deotyma (właśc. Łuszczewska, Jadwiga; 1834-1908); "Pamiętnik 1834-1897"; "Zwierciadlana zagadka"; natchnienie pisarza; improwizacje; writer`s inspiration; improvisations